GP178 Morphological features of chronic esophagitis in children with concomitant allergic diseases are interrelated with the level of cytokines and neuropeptides. (June 2019) - novikova, valeria; Anichkov, Nikolay; Nevskaia, Elena; Listopadova, Anastasia; Zamiatina, Yulia; Gurina, Olga; Varlamova, Olga; Blinov, Aleksey
Abstract : Introduction: IgE-mediated as well as non-IgE-mediated inflammation to the mucous membranes of the gastrointestinal tract is possible in children with allergic diseases. Purpose of the study: We investigated the morphological features of chronic esophagitis in children with atopic dermatitis (AtD) and bronchial asthma (BA) taking in account the cytokine status (IL-4, IL-5 and IL-13), the level of markers of eosinophilic inflammation (eosinophilic cationic ECP protein and eosinophilic neurotoxin EDN) and neuropeptides (neuropeptide Y (NPY) and substance P (SP)). Patients and methods: Study included 61 children (mean age 13.9 ± 2.36 years) having morphologically verified chronic esophagitis. 20 children suffered from concomitant AtD, 21 had esophagitis with BA. 20 children had esophagitis without concomitant atopic diseases. All children have undergone esophagogastroduodenoscopy and sampling of mucosal biopsy material from the middle third of the esophagus. Histologically we evaluated dystrophic, regenerative, inflammatory changes, vascular disorders and defects of the mucous membrane. In all children, the level of total IgE was determined and a blood test for IL-4, IL-5 and IL-13, ECP, EDN, NPY and SP was performed by ELISA. The statistical results were estimated by use of the program Stat Soft Statistica 12.0. for Windows-10. Research results: Morphological features of esophagitis in all studied groups equally frequent. The average level of total IgE in children with AtD and esophagitis was 186.6 ± 126.6 U/ml.; in the group of children with BA was 331, 5 ± 238, 6 U/ml. All children with esophagitis without atopic diseases had a level of total IgE within the normal range. In AtD, IL-4 levels (1.08 ± 0.47 pg/ml and 1.91 ± 0.88 pg/ml, p<0.05), IL-5 (21.39 ± 15.47 pg/ml and 1.91 ± 0.88 pg/ml, p<0.05), IL-13 (1.72 ± 1.55 pg/ml and 12.11 ± 6.10 pg/ml, p<0.05), EDN (47.70 ± 34.83 pg/ml and 119.00 ± 64.26 pg/ml, p<0.05) and NPY (40.62 ± 20.55 pg/ml and 160.44 ± 144.44 pg/ml, p<0.005) were lower than with the combination of esophagitis with BA and had no differences with the group of children without atopy. Correlative relationship between morphological and immunological parameters in patients with atopy was found. Conclusion: Esophagitis in children with bronchial asthma is accompanied by higher levels of IgE and more pronounced changes in cytokine status than in atopic dermatitis. The correlative relationships between morphological and immunological parameters in patients with atopy allow to suggest the significant role of allergic and neuropeptide inflammation of the esophageal mucosa in children with allergic diseases.